The regulatory effects of bioactive polysaccharides on intestinal function and bile acids: chemical structures, bioactivities, and mechanisms - Wang, Anqi; Xiong, Wugui; Li, Jing; Hu, Yingfan; Zou, Liang; Liu, Ying (Frontiers in Nutrition, 2024)
Polysaccharides is one of important components of human diet carrying with a wide range of biological activities, especially for the activities in the improvement of inflammation of digestive system and metabolic diseases. Among all the reported bioactivities of polysaccharides, the regulation effects in intestinal function and bile acids in experiments are gradually attracting more and more researchers' attention. Bile acids, the main components of intestinal lipid digestive fluid, are also the key signal factors for metabolic homeostasis and impact on body health. Polysaccharides usually directly or indirectly interact with the gut and gut microbiota to participate in the regulation process of reabsorption, metabolism and excretion of bile acids in human, and thus exerting their intervention role for human diseases. In this paper, we comprehensively reviewed the effects of bioactive polysaccharides in regulation of intestinal function and bile acids. The chemical structures, bioactivities and potential mechanisms for their activities are also reviewed, which aims to provide a comprehensive reference for the future researches in the activities and mechanisms of polysaccharides, and to provide important strategies and thoughts for the development of bioactive polysaccharides for preventing inflammatory and metabolic diseases.